The Correlation Between Test and Non-Test Assessments in the Structure and Function of Plants Course - Rusyati, Lilit; Nurismawati, Riana; Pujirana, Andi Isni (International Journal of Biology Education Towards Sustainable Development, 2025)
The problem in this case is the requirement to examine the similarity between the students' theoretical knowledge (determined by the test results) and their competencies and engagement (determined by the results of the non-test assessment). The purpose of this study is to examine the relation between the test results and the non-test results among students in the Plant Structure and Function class. The data collected in this study came from 131 prospective junior high school teachers in the field of sciences. The results of the analysis in this case show that the Test results are positively associated and strongly significant with the results of the Non-Test results in this study with the value of the correlation coefficient (r = 0.357) and significance (p = 0.000). In fact, there is no causal relationship between the results in the two tests but there is an associative relation. The results in this study can be considered as a source for the teachers in constructing a comprehensive evaluation system.